SOCIOECONOMIC FACTORS INFLUENCING ADOPTION OF RECOMMENDED IRISH POTATO PRODUCTION TECHNOLOGIES AMONG WOMEN FARMERS IN PLATEAU STATE, NIGERIA - Yakubu, K.; Danwanka, H.; Abu, I. A. (Nigerian Journal of Agriculture and Agricultural Technology, 2023)
The study examined the factors influencing adoption of irish potato recommended production technologies among women farmers in plateau state, Nigeria. A multi stage sampling technique was used in selecting 229 respondents from the study area. Data were collected using structured questionnaire and were analyzed using descriptive and inferential statistics. The result reveal that 32.8%, 31.9% and 23.1% of the respondents were within the ages of 28-37 years and 38-47 years and 18-27 years respectively. Almost half (48.9%) of the respondents had household size between 3-4 persons. Majority (53.3%) of the respondents had farm size of between 1-2 hectare and a reasonable proportion (36.2%) have less than 1 hectare. Most (75.5%) of the respondents were married. The result also shows that almost half (46.7%) of the respondents had attended secondary school. The result further shows that more than half (52.4%) of the respondents were members of cooperatives and a reasonable proportion (47.6%) of the respondents does not belong to any cooperative societies. Almost half (49.3%) and a reasonable proportion (33.6%) of the respondents were artisans and livestock producers as their secondary occupation. The result also indicated that 44.5% and 38% of the respondents had a farming experience of 7-13 years and 1-6 years. A reasonable proportion of 42.8% harvested more than 12 bags. Majority (73.4%) of the respondents had an annual income of ₦50,000-₦100,000. Majority (85.2%) of the respondents had access to extension, while 14.8% of the respondents had no access to extension. About 38.4% and 32.8% of the respondents received extension visits quarterly and annually respectively in the study area. The result of regression analysis revealed that yield, land ownership, extension visit and information sources were significant (P<0.01) in influencing the adoption of potato production technologies. The result further revealed that, age, farm size, farming experience and income were also significant (P<0.05) in influencing the adoption of recommended irish potato technologies. However, Inadequate capital (67.3%), flood (65.1%), inadequate farmland (62.9%), and scarcity of improved planting materials (62.4%) were the major constraints affecting women’s adoption of recommended technologies which were ranked 1st, 2nd, 3rd, and 4th respectively. The study concluded that land ownership, yield, income, access to extension, frequency of extension visit, sources of information, age, farm size and farming experience were the factors that significantly influence the adoption of recommended Irish potato production practices. The study recommended that there is need for government and non-governmental organizations to make credit facilities available and accessible to farmers at single digit interest and also there is need for farmers to be trained on yield-raising technologies and other technologies that can positively contribute to high productivity among farmers.